THE EFFECT OF THE THINK TALK WRITE TYPE COLLABORATIVE LEARNING MODEL ON THE OUTCOMES OF LEARNING TO WRITE POETRY IN GRADE VII STUDENTS OF SMP SASTA GKPS 3 PEMATANGSIANTAR - Erri Kisando Sinaga; Mulyono (RADJA PUBLIKA, 2025)
This study aims to determine whether there is a significant influence in learning to write poetry on seventh grade students of GKPS 3 Pematangsiantar Private Middle School. This study was conducted in 2025 at GKPS 3 Pematangsiantar Private Middle School. This study is a quantitative study with an experimental approach and uses a one group pretest-posttest model. Furthermore, this study will be compared with related test samples at a significant level or a level of 0.05 (95%). The result is the average pretest value = 43.5 and the average posttest value = 76.5. From the data analysis, the research hypothesis was tested using the